(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Political and legal views of Abai was progressive. He tried to modernize the good traditions of the beys, a unique judicial institution of the Kazakh people, he employed, allowed all kinds of domestic disputes, carried out legal activities. Studying the rich heritage of beys, Abay makes his findings, will form its own political and legal ideas.The aim of the research work – conduct a retrospective analysis of political and legal ideas of Abai, to consider features of the traditional socio-legal Institute of the Kazakh court of biys and judicial reform of the Russian Empire. The main directions and ideas for research – this paper analyzes the influence of the legal ideas of Abai on improving the political and legal literacy of his contemporaries and followers, logisim spiritual guide of his people in tough colonial policy of tsarist Russia. Scientific and practical significance of the work in the political and legal ideas of Abai accumulated a rich tradition of Kazakh biys, especially valuable views and ideas of the great thinker about politics, power, law, freedom, law. Research methodology: historical method and retrospective analysis. Key words: legal ideas of Abai, political views, suganya reform, colonial policy.